A novel benzothiazole derivative induces apoptosis via the mitochondrial intrinsic pathway producing antitumor activity in colorectal cancer - Zhou, Jing; Zhao, Rongce; Zhou, Haoxuan; Yang, Shuping; Tao, Feiyan; Xie, Yongmei; Wang, Hongli; Yun, Jingping (Frontiers in Pharmacology, 2023)
Background: Colorectal cancer (CRC) is one of the most common malignancies causing the third highest mortality rate in the world. It is particularly urgent to explore effective therapeutic strategies to overcome this disease. We identified a novel benzothiazole derivative (BTD) that may serve as a potentially effective agent against CRC. Method: MTT assays, cell colony formation assays, EdU staining assays, flow cytometry, RNA-seq, Western blotting, and migration and invasion assays were used to examine the effects of BTD on cell proliferation, apoptosis, metastasis, and the cell cycle. The antitumor activity of BTD in vivo was investigated in a CT26 tumor-bearing mouse model. Immunohistochemistry (IHC) was performed to examine the protein expression in mouse tumors. Hematology, biochemical analysis, and H&E staining were used to assess the biosafety of BTD. Results: We observed that BTD suppressed cell proliferation and metastasis and promoted the apoptosis of tumor cells in vitro. Treatment with BTD at a tolerable dose significantly reduced tumor growth in CT26-tumor-bearing mice and appeared to be safe. Treatment of BTD induced apoptosis by increasing the generation of reactive oxygen species (ROS) and evoking the loss of mitochondrial transmembrane potential. Overall, BTD suppressed cell proliferation and metastasis, and induced apoptosis of colorectal tumor cells through the ROS–mitochondria-mediated apoptotic pathway. The preliminary proof of the antitumor activity and relative safety of BTD were validated in a mouse model. Conclusion: Our findings suggest that BTD could serve as a potentially safe and effective candidate for CRC treatment.